Halal Management Based on Local Assistance from the Economic Empowerment Perspective of the Ministry of Tourism of the Republic of Indonesia - Yusuf Ali; Dian Damayanti; Ghazalie; Yulian Azhari (Communications of International Proceedings, 2021)
Halal management based on local wisdom at the Ministry of Tourism of the Republic of Indonesia. This research uses qualitative method. The results showed that the halal tourism management set by the Ministry of Tourism of the Republic of Indonesia is expected to be able to be responded to by the local community; Local wisdom of the local community in responding to plans to determine halal tourism in improving economic living standards, can help the economy and tourism development without eliminating existing local wisdom; The results achieved by the community regarding regional economic empowerment in the development of halal tourism and related agencies cooperate with each other and provide socialization with the local community. This tourism development is recommended to improve the economy. where the goals and objectives of the policy must be transmitted to the target group, reducing the reduction in implementation distortions, reducing the level of public awareness is needed coaching and counseling so that citizens really know or understand the uses or benefits of implementation so that the citizens volunteer lyobey and obey existing rules, and reduce m orbidity and mortality. to create a healthy Indonesia, protect and provide services to the community, and maintain health by upholding human rights.
Keywords: Halal tourism; Management; Local Wisdom